Soveršenstvovanie upravlenija sportivnoj podgotovkoj junych chokkeistov 13-14 let na osnove emocional'nogo i social'nogo intellekta - Kondratyev, A. V.; Kuzmenko, G. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The purpose of the study: identification the relationships between the emotional and social intelligence of young hockey players aged 13-14, determination the nature of their clustering, and highlighting the key factors that ensure adaptation and meaningful management of sports improvement. The position on the essence of sports activity management where the leading subject is a young athlete has been substantiated. The problem of coaches` using the strategy of isolation from young hockey players demonstrating undesirable results of sports activity is revealed, which does not cause the athlete to mobilize efforts, but, on the contrary, creates conditions for migration to other sports teams, which increases the significance of the directed development of emotional intelligence, structurally included in the social intelligence of the person. There were revealed reliable connections between the indicators of young hockey players emotional intelligence and manifestations of the volitional sphere, organizational skills, control-evaluative activity, the personality business status and achievement motivation co-organizing the self-management process by sports improvement. The conjugation clusters of the studied variables are defined where in basic: the business status of the young hockey player interfaced with the attitude in the "coach-athlete" system; "psychological atmosphere in the team" - with social intelligence; verbal intelligence integrates with emotional intelligence. Achievement motivation is embedded by the upper cluster in all manifestations of emotional and social intelligence in sports. It serves as the basis for personal development and actualizes the importance of psychologically competent communication in the "coach-athlete" system. The most important factor weights are: the final and emotional indicators of the "coach-athlete" relationship; psychological atmosphere in the team; social and emotional intelligence. Recommendations on psychological and pedagogical support for 25% of young hockey players demonstrating low indicators of the studied qualities and limiting the resources of sports training self-management are given.